Comparing the associations of central venous pressure and pulmonary artery pulsatility index with postoperative renal injury - Wei, Johnny; Houchin, Abigail; Nazir, Niaman; Leonardo, Vincent; Flynn, Brigid C. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Cardiac surgery-associated acute kidney injury (CS-AKI) is associated with significant morbidity and mortality. We investigated the association of postoperative central venous pressure (CVP) and pulmonary artery pulsatility index (PAPi) with the development of CS-AKI. Methods: This was a single-center, retrospective cohort study of patients undergoing cardiac surgery. CVP and PAPi were acquired hourly postoperatively and averaged for up to 48 hours. PAPi was calculated as [(Pulmonary Artery Systolic Pressure – Pulmonary Artery Diastolic Pressure) / CVP]. The primary aim was CS-AKI. Secondary aims were need for renal replacement therapy (RRT), hospital and 30-day mortality, total ventilator and intensive care unit hours, and hospital length of stay. Logistic regression was used to calculate odds of development of renal injury and need for RRT. Results: 1288 patients were included. The average postoperative CVP was 10.3 mmHg and average postoperative PAPi was 2.01. Patients who developed CS-AKI (n=384) had lower PAPi (1.79 vs 2.11, p<0.01) and higher CVP (11.5 mmHg vs 9.7 mmHg, p<0.01) than those who did not. Lower PAPi and higher CVP were also associated with each secondary aim. A standardized unit decrease in PAPi was associated with increased odds of CS-AKI (OR 1.39, p<0.01) while each unit increase in CVP was associated with both increased odds of CS-AKI (OR 1.56, p<0.01) and postoperative RRT (OR 1.49, p=0.02). Conclusions: Both lower PAPi and higher CVP values postoperatively were associated with the development of CS-AKI but only higher CVP was associated with postoperative RRT use. When differences in values are standardized, CVP may be a more associated with development of CS-AKI when compared to PAPi.